Experience of intense pulsed light use in a patient with rosacea - E. E. Zhiltsova; K. V. Mezhevaya; S. A. Isakov; N. P. Ermoshina (Лечащий Врач, 2021)
This article discusses in detail the clinical case of a patient diagnosed with rosacea, hypertrophic subtype, severe course. This patient was given a course of phototherapy with intense pulsed light. The clinical and dermatoscopic picture, the parameters of the procedure, as well as the effect after treatment are described in detail. Rosacea is a chronic dermatosis, it has a variety of clinical forms. This disease is an urgent problem of modern dermatovenerology due to the presence of cosmetic defects in patients.